Islamic Jurisprudence Motivation and Self-Awareness in the Discipline of Congregational Prayers of Islamic Students - Muhammad Fauzan Rivaldi; Murni Karomah; Retno Widyaningrum; Mohammad Rohman Rifai (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article examines the influence of motivation to understand prayer jurisprudence based on Fathul Qarib and self-awareness on female santri’s discipline in congregational prayer. This quantitative ex post facto study was conducted at Pondok Pesantren Al-Barokah Ponorogo during the 2025/2026 academic year. The population consisted of 130 female santri, while 96 respondents were selected through random sampling using Slovin’s formula with a 5% margin of error. Data were collected through observation and Likert-scale questionnaires and analyzed using descriptive statistics, classical assumption tests, simple linear regression, and multiple linear regression with IBM SPSS Statistics 25. The findings show that motivation to understand prayer jurisprudence statistically accounts for 59.1% of the variance in congregational prayer discipline, whereas self-awareness provides a stronger contribution of 66.7%. Simultaneously, both variables explain 70.6% of the variance. These findings indicate that mature worship discipline emerges from the integration of the cognitive-normative foundation of fiqh and santri’s internal self-regulation. The study theoretically proposes a hybrid-reflective fiqh curriculum framework that combines textual study of Fathul Qarib, contextual application, self-reflection, and self-monitoring to strengthen consistent congregational worship.